2014
DOI: 10.1016/j.jmbbm.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

An “in vitro” experimental model to predict the mechanical behavior of macroporous scaffolds implanted in articular cartilage

Abstract: A model is proposed to assess mechanical behaviour of tissue engineering scaffolds and predict their performance "in vivo" during tissue regeneration. To simulate the growth of tissue inside the pores of the scaffold, the scaffold is swollen with a Poly (Vinyl alcohol) solution and subjected to repeated freezing and thawing cycles. In this way the Poly (Vinyl alcohol) becomes a gel whose stiffness increases with the number of freezing and thawing cycles. Mechanical properties of the construct immersed in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…shown that the gel enters all macro and micro pores of the PCL scaffold 16 . The calculated porosity according to equation 1 was zero, within the errors of the calculations, which probes the effectiveness of the vacuum filling of the PVA solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…shown that the gel enters all macro and micro pores of the PCL scaffold 16 . The calculated porosity according to equation 1 was zero, within the errors of the calculations, which probes the effectiveness of the vacuum filling of the PVA solution.…”
Section: Resultsmentioning
confidence: 99%
“…PVA has the special characteristic of physically cross-link with repeating cycles of freezing and thawing 49 . In a previous work we showed that the PCL/PVA construct reaches values of elastic modulus in the range of natural articular cartilage after 6 cycles of freezing and thawing 16 . By performing unconfined and confined compression tests of the different PCL/PVA constructs the permeability and mechanical behavior have been investigated.…”
Section: Introductionmentioning
confidence: 93%
“…The mechanical properties of the PCL and PVA construct reached values of natural articular cartilage and meniscus. The PCL and PVA construct is then considered suitable as an in vitro model for simulating the growing cartilage inside of the scaffold of the PCL scaffold 27 In the present work the same protocol was applied to obtain PCL -PVA constructs, whose fatigue mechanical properties were measured.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies our group filled a porous PCL scaffold with a PVA gel physically cross-linked by different cycles of freezing and thawing and evaluated its mechanical properties. It was possible to tailor the elastic modulus of the PCL-PVA construct to reach values characteristic of natural articular cartilage after six cycles of freezing and thawing (Vikingsson et al 2014). The outcome is an cartilage model mimicking the behavior of the growing ECM inside the pores of the implanted scaffold in a cartilage defect.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the empty scaffold or filled with water has been compared to the behavior of the scaffold filled with hydrogel after six cycles of freezing and thawing, to mimic the characteristics of natural articular cartilage (Vikingsson et al 2014). This experimental study aims to predict the mechanical performance of a macro and micro porous PCL scaffold in a cartilage defect.…”
Section: Introductionmentioning
confidence: 99%